The Influence of Education Level, Knowledge, and Pregnancy Spacing on the Incidence of Anemia Among Pregnant Women - Samsir; Ainal Mardiah; Yully Asmariana; Mahfuzhah Deswita Puteri; Yunita Kristina (CV. Get Press Indonesia, 2024)
A pregnant woman is considered to have anemia if her hemoglobin level is less than 11 grams/dl. This disease causes problems for the mother and the fetus, including infection, bleeding, birth defects, and possibly maternal and infant death. Purpose : The purpose of this research is to identify the variables linked to the prevalence of anemia in expectant mothers at the Community Health Center. Methods : This research is cross-sectional and analytical in nature. All pregnant women in the vicinity of the Bungus Community Health Center made up the study population, and 80 pregnant women were chosen as a sample using the incidental sampling technique. Questionnaires and a digital hemoglobin equipment were used to measure hemoglobin levels. The Chi-Square statistical test was used to conduct the analysis both univariately and bivariately. Result : According to the findings, anemia affected 66.2% of expectant mothers. Factors found to be associated with the incidence of anemia were education level (p = 0.00) and pregnancy spacing (p = 0.02), while knowledge level did not have a significant relationship (p = 0.073). Implications : The study's findings indicate that while there is no appreciable relationship between knowledge level and anemia incidence, the incidence of anemia in pregnant women is connected with both pregnancy spacing and educational attainment. Conclusion : To prevent anemia, it is hoped that health professionals will take a more active role in educating expectant mothers about the value of proper diet and prenatal monitoring.